Innovations for Metropolitan Areas. Intelligent Solutions for Mobility, Logistics and Infrastructure designed for Citizens. - (:unkn) unknown (Springer Gabler, 2020)
This book presents human-centered concepts and solutions for mobility, logistics and infrastructure that will make our growing metropolitan areas more livable and sustainable.The still accelerating megatrend of urbanization is leading to constantly growing metropolitan areas. This creates a whole series of challenges for municipalities, as well as citizens, such as overcrowded traffic routes, limited building space and an increasingly difficult supply situation. With this book we want to answer the following question: How can people live in densely populated areas and meet their needs in terms of mobility, freedom, self-determination, security, prosperity, communication or in other words: how can metropolitan regions be made humane? The answer to this question requires innovative ideas and approaches in various areas: (a) Sustainable designs of infrastructure, (b) Economically and ecologically efficient logistics and mobility approaches, (c) Intelligent applications for navigation and communication. All these ideas must be measured against the needs of citizens and should thus be developed following a human-centered design approach. This ensures that innovative solutions will be widely accepted by the public. In addition, they also have the potential to turn citizens into active co-designers of future metropolitan areas.
Keywords: Stadtentwicklungskonzept; Metropolregion; Verstädterung; Urbanisierung; Mobilität; Digitalisierung; Stadtverkehr; Logistik; Effizienz; Transformation; Prozesssteuerung; Navigationssystem; Kommunikation; Nachhaltige Entwicklung